Psychoanalysis and health: the movement of the word in occupational health - de Oliveira, Sidney (Revista de Psicologia, 2013)
The experience of the word among health workers and patients is a symptom of the biological context, sociological and psychological. The analysis of the word must be made in form and content. This work was carried out as a very relevant investigative problems among health workers and patients in a center of public health. This article discusses occupational health in the contradictions between organizational management, personal commitment and industrial capitalism. The occupational health proves to be a symptom of the biological context, social and psychological. The pursuit of excellence in performance invaded industrial society and occupational health in pursuit of continuous improvement of performance. Emphasized here that the behavioral strategies of domination in organizations aimed to, from the rise of capitalism, individuals adapt to hegemonic ideology.